Thermosetting resin composition, prepreg, resin film, laminate, printed wiring board, antenna device, antenna module, and communication device

The thermosetting resin composition with high dielectric constant inorganic fillers and molybdenum compounds addresses drilling issues in high dielectric constant materials, enhancing drillability and insulation reliability for high-frequency antenna modules.

JP2025010821APending Publication Date: 2025-01-23RESONAC CORP

Patent Information

Application Number
JP2023113059
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

High dielectric constant materials used to increase the dielectric constant (Dk) of substrate materials often have high Mohs hardness, leading to deteriorated drilling workability and cracks during laminate drilling, which affects insulation reliability.

Method used

A thermosetting resin composition containing high dielectric constant inorganic fillers such as titanium-based and zircon-based materials, combined with a molybdenum compound, to enhance drilling workability while maintaining a high dielectric constant and low dielectric loss tangent.

Benefits of technology

The composition provides excellent drillability, improving insulation reliability and enabling the production of high-frequency antenna modules with reduced size and enhanced communication quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010821000001
    Figure 2025010821000001
  • Figure 2025010821000002
    Figure 2025010821000002
Patent Text Reader

Abstract

To provide a thermosetting resin composition which is useful as an antenna module and is excellent in drilling property, and a prepreg, a resin film, a laminate, a printed wiring board, an antenna device, an antenna module, and a communication device, which are obtained using the thermosetting resin composition.SOLUTION: A thermosetting resin composition contains (A) a thermosetting resin, and (B) one or more kinds of high dielectric constant inorganic fillers selected from the group consisting of a titanium-based inorganic filler and a zirconium-based inorganic filler, and further contains (X) a molybdenum compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a thermosetting resin composition, a prepreg, a resin film, a laminate, a printed wiring board, an antenna device, an antenna module, and a communication device. [Background technology]

[0002] In recent years, mobile terminals such as smartphones have become widespread, and as a result of technological innovations such as the Internet of Things (IoT), the number of home appliances and electronic devices with wireless communication functions is increasing. This has led to an increase in communication traffic on wireless networks, raising concerns that communication speed and quality may decline. To solve this problem, the development of the fifth generation mobile communication system (hereinafter sometimes referred to as "5G") is underway, and it is already being used. 5G uses multiple antenna elements to perform advanced beamforming and spatial multiplexing, and uses millimeter wave signals with higher frequencies, such as several tens of GHz, in addition to the conventionally used 6 GHz frequency signals. This is expected to increase communication speeds and improve communication quality. Hereinafter, frequencies above 10 GHz are referred to as high frequencies.

[0003] As such, 5G requires that antenna modules be able to handle high-frequency signals, and to achieve this, the dielectric constant (Dk) and dielectric dissipation factor (Df) of the laminate in the high-frequency band must be low, and in particular, the dielectric dissipation factor (Df) must be low. Since high-frequency radio waves have high linearity, signals carried on high-frequency radio waves tend to be easily blocked by obstacles such as buildings. Therefore, in order to avoid such blocking, multiple antenna devices are mounted on an antenna module. Since the antenna device can be made smaller by increasing the relative dielectric constant (Dk) of the substrate material, increasing the relative dielectric constant (Dk) is effective for mounting multiple antenna devices, and also leads to the miniaturization of the antenna module and, ultimately, the miniaturization of the communication device. Therefore, the laminate used in the antenna module capable of handling high-frequency signals is required to have a specific relative dielectric constant (Dk) and a low dielectric loss tangent (Df).

[0004] One method for increasing the relative dielectric constant (Dk) of the substrate material is to use a high dielectric constant material (see, for example, Patent Document 1). The small antenna described in Patent Document 1 is manufactured by laminating a first dielectric layer made of a low dielectric constant material between second and third dielectric layers made of a high dielectric constant material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2005 / 101574 Summary of the Invention [Problem to be solved by the invention]

[0006] However, high dielectric constant materials for increasing the relative dielectric constant (Dk) of the board material usually have a high Mohs hardness, and therefore there is concern about deterioration of drilling processability. Since deterioration of drilling processability is a cause of cracks occurring at the interface between the resin composition and the glass cloth when holes are drilled in the laminate, deterioration of drilling processability leads to deterioration of insulation reliability. Therefore, there is a need to develop a technology that improves drilling processability while using high dielectric constant materials.

[0007] In view of the current situation, an object of the present disclosure is to provide a thermosetting resin composition that is useful for antenna modules and has excellent drill processability, as well as to provide a prepreg, a resin film, a laminate, a printed wiring board, an antenna device, an antenna module, and a communication device obtained using the thermosetting resin composition. [Means for solving the problem]

[0008] As a result of extensive research, the present inventors have found that the above-mentioned object can be achieved by using the thermosetting resin composition and the like according to the present disclosure.

[0009] The present disclosure includes the following embodiments [1] to

[17] . [1] (A) Thermosetting resins, and (B) one or more high dielectric constant inorganic fillers selected from the group consisting of titanium-based inorganic fillers and zircon-based inorganic fillers; A thermosetting resin composition comprising: The thermosetting resin composition further contains (X) a molybdenum compound. [2] The thermosetting resin composition according to the above [1], wherein the component (X) is at least one selected from the group consisting of molybdenum oxides, molybdic acid compounds, molybdenum boride, molybdenum disilicide, molybdenum nitride, and molybdenum carbide. [3] The thermosetting resin composition according to the above [2], wherein the molybdenum oxide is molybdenum trioxide. [4] The thermosetting resin composition according to the above [2], wherein the molybdic acid compound is at least one selected from the group consisting of zinc molybdate, ammonium molybdate, magnesium molybdate, calcium molybdate, barium molybdate, sodium molybdate, potassium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, and silicomolybdic acid. [5] The thermosetting resin composition according to any one of the above [1] to [4], wherein the titanium-based inorganic filler is at least one selected from the group consisting of titanium dioxide and metal titanates. [6] The thermosetting resin composition according to [5] above, wherein the metal titanate is at least one selected from the group consisting of alkali metal titanates, alkaline earth metal titanates, and lead titanate. [7] The thermosetting resin composition according to any one of the above [1] to [6], wherein the zircon-based inorganic filler is an alkali metal zirconate. [8] The thermosetting resin composition according to any one of the above [1] to [7], wherein the content of the component (X) is 0.1 to 10 volume % based on the total amount of solids in the thermosetting resin composition. [9] The thermosetting resin composition according to any one of the above [1] to [8], wherein the component (A) comprises one or more resins selected from the group consisting of epoxy resins, maleimide compounds, polyphenylene ether resins, phenolic resins, polyimide resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, dicyclopentadiene resins, silicone resins, triazine resins, and melamine resins.

[10] The thermosetting resin composition according to any one of the above [1] to [9], wherein the component (A) contains a polyphenylene ether resin having ethylenically unsaturated bond-containing groups at both ends.

[11] A prepreg comprising the thermosetting resin composition according to any one of the above [1] to

[10] or a semi-cured product of the thermosetting resin composition.

[12] A resin film comprising the thermosetting resin composition according to any one of the above [1] to

[10] or a semi-cured product of the thermosetting resin composition.

[13] A laminate comprising a cured product of the thermosetting resin composition according to any one of the above [1] to

[10] and a metal foil.

[14] A printed wiring board having a cured product of the thermosetting resin composition according to any one of [1] to

[10] above.

[15] An antenna device having the laminate described in

[13] above.

[16] An antenna module comprising a power supply circuit and the antenna device described in

[15] above.

[17] A communication device comprising a baseband signal processing circuit and the antenna module described in

[16] above. Effect of the Invention

[0010] The present disclosure makes it possible to provide a thermosetting resin composition having excellent drill processability and useful for antenna modules, as well as to provide prepregs, resin films, laminates, printed wiring boards, antenna devices, antenna modules, and communication devices obtained using the thermosetting resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the numerical ranges described in the present disclosure, the upper or lower limit of the numerical range may be replaced with the values ​​shown in the examples. In addition, the lower and upper limits of a numerical range may be arbitrarily combined with the lower or upper limit of another numerical range. In the expression of a numerical range "AA to BB", the numerical values ​​AA and BB at both ends are included in the numerical range as the lower and upper limits, respectively. In the present disclosure, for example, the description "10 or more" means 10 and a numerical value exceeding 10, and the same applies when the numerical values ​​are different. Also, for example, the description "10 or less" means 10 and a numerical value less than 10, and the same applies when the numerical values ​​are different. In addition, each component and material exemplified in this disclosure may be used alone or in combination of two or more types, unless otherwise specified. In this disclosure, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified.

[0012] In the present disclosure, the term "resin component" refers to all components of the solid content constituting the resin composition, excluding inorganic compounds such as a high dielectric constant inorganic filler described below, a molybdenum compound described below, and an inorganic filler described below. In the present disclosure, the term "solid content" refers to components other than the organic solvent described below, and components that are liquid at 25°C are also considered to be solid content. The expression "containing XX" described in the present disclosure may mean that XX is contained in a reacted state when XX is reactive, or may mean that XX is simply contained as it is, or may include both of these aspects. Any combination of the descriptions in this disclosure is also included in this disclosure and this embodiment.

[0013] [Thermosetting resin composition] The thermosetting resin composition of the present embodiment is as follows. (A) a thermosetting resin (hereinafter, sometimes referred to as component (A)); and (B) one or more high dielectric constant inorganic fillers selected from the group consisting of titanium-based inorganic fillers and zircon-based inorganic fillers (hereinafter, sometimes referred to as component (B)); A thermosetting resin composition comprising: The thermosetting resin composition further contains (X) a molybdenum compound [hereinafter, sometimes referred to as component (C)]. Hereinafter, the components contained in the thermosetting resin composition of the present embodiment will be described in detail in order.

[0014] ((A) Thermosetting resin) Examples of the (A) component include epoxy resins, maleimide compounds, polyphenylene ether resins, phenolic resins, polyimide resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, dicyclopentadiene resins, silicone resins, triazine resins, and melamine resins, and it is preferable that the (A) component contains at least one selected from these. It is more preferable that the (A) component contains at least one selected from the group consisting of epoxy resins, maleimide compounds, and polyphenylene ether resins, and from the viewpoints of low thermal expansion, high frequency characteristics, and the like, it is even more preferable that the (A) component contains at least one selected from the group consisting of maleimide compounds and polyphenylene ether resins. As the component (A), one type may be used alone, or two or more types may be used in combination.

[0015] The epoxy resin is preferably an epoxy resin having two or more epoxy groups in one molecule. Here, the epoxy resin is classified into glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, etc. Among these, glycidyl ether type epoxy resin is preferable. Epoxy resins are also classified into various epoxy resins depending on the difference in the main skeleton, and each of the above types of epoxy resins is further classified into bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, and bisphenol S type epoxy resins; alicyclic epoxy resins such as dicyclopentadiene type epoxy resins; aliphatic linear epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, phenol aralkyl novolac type epoxy resins, and biphenyl aralkyl novolac type epoxy resins; stilbene type epoxy resins; naphthalene skeleton-containing epoxy resins such as naphthol novolac type epoxy resins and naphthol aralkyl type epoxy resins; biphenyl type epoxy resins; xylylene type epoxy resins; and dihydroanthracene type epoxy resins.

[0016] The maleimide compound preferably includes at least one selected from the group consisting of maleimide compounds having one or more (preferably two or more) N-substituted maleimide groups and derivatives thereof. The maleimide compound having one or more N-substituted maleimide groups is not particularly limited, and examples thereof include aromatic maleimide compounds having one N-substituted maleimide group bonded to an aromatic ring, such as N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, and N-benzylmaleimide; bis(4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl- Examples of the aromatic bismaleimide compounds include aromatic bismaleimide compounds having two N-substituted maleimide groups bonded to an aromatic ring, such as 1,3-phenylene bismaleimide, m-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, and indane ring-containing bismaleimide; aromatic polymaleimide compounds having three or more N-substituted maleimide groups bonded to an aromatic ring, such as polyphenylmethane maleimide and biphenyl aralkyl maleimide; and aliphatic maleimide compounds such as N-dodecylmaleimide, N-isopropylmaleimide, N-cyclohexylmaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, and pyrrolidine binder type long-chain alkyl bismaleimide. Among these, from the viewpoints of compatibility with other resins, adhesion to conductors, heat resistance, low thermal expansion, and mechanical properties, aromatic bismaleimide compounds having two N-substituted maleimide groups bonded to an aromatic ring are preferred, and 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane is more preferred. The maleimide compound having one or more N-substituted maleimide groups may be a maleimide compound having two or more N-substituted maleimide groups, and in this case, the maleimide compound having two or more N-substituted maleimide groups preferably has nitrogen atoms of at least two maleimide groups linked to each other via an organic group. Examples of the organic group include an aliphatic hydrocarbon group, an aromatic hydrocarbon group, and a group combining these.

[0017] Examples of the derivatives of the maleimide compound include an addition reaction product between a maleimide compound having one or more (preferably two or more) N-substituted maleimide groups and an amine compound such as a monoamine compound or a diamine compound (hereinafter, sometimes referred to as a "modified maleimide compound"). Examples of the monoamine compound include monoamine compounds having an acidic substituent, such as o-aminophenol, m-aminophenol, p-aminophenol, o-aminobenzoic acid, m-aminobenzoic acid, p-aminobenzoic acid, o-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, 3,5-dihydroxyaniline, and 3,5-dicarboxyaniline. Examples of the diamine compound include 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylpropane, 2,2'-bis(4,4'-diaminodiphenyl)propane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylethane, 3,3'-diethyl-4,4'-diaminodiphenylethane, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl Examples of the aromatic diamine compounds include aminodiphenyl thioether, 3,3'-dihydroxy-4,4'-diaminodiphenylmethane, 2,2',6,6'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,3'-dibromo-4,4'-diaminodiphenylmethane, 2,2',6,6'-tetrachloro-4,4'-diaminodiphenylmethane, and 2,2',6,6'-tetrabromo-4,4'-diaminodiphenylmethane; and siloxane diamines. The maleimide compound preferably includes an addition reaction product between a maleimide compound having two or more N-substituted maleimide groups and an amine compound, and more preferably includes an addition reaction product between a maleimide compound having two or more N-substituted maleimide groups and a diamine compound including a siloxane diamine.

[0018] The polyphenylene ether resin may be an unmodified polyphenylene ether resin or a polyphenylene ether resin having an ethylenically unsaturated bond-containing group at the end, with the latter being preferred. The polyphenylene ether resin having an ethylenically unsaturated bond-containing group at the end is preferably a polyphenylene ether resin having an ethylenically unsaturated bond-containing group at both ends. Here, the "ethylenically unsaturated bond-containing group" refers to a substituent containing a carbon-carbon double bond capable of an addition reaction, and does not include a double bond of an aromatic ring. Examples of the ethylenically unsaturated bond-containing group include unsaturated aliphatic hydrocarbon groups such as vinyl groups, allyl groups, 1-methylallyl groups, isopropenyl groups, 2-butenyl groups, 3-butenyl groups, and styryl groups; and groups containing a heteroatom and an ethylenically unsaturated bond, such as maleimide groups and (meth)acryloyl groups. The ethylenically unsaturated bond-containing group is preferably a group containing a hetero atom and an ethylenically unsaturated bond, more preferably a (meth)acryloyl group, and even more preferably a methacryloyl group. In the present disclosure, the term "(meth)acryloyl group" is a general term for an acryloyl group and a methacryloyl group.

[0019] As the thermosetting resin other than the epoxy resin, the maleimide compound, and the polyphenylene ether resin, known resins can be used, and commercially available products can also be used.

[0020] ((A) Thermosetting resin content) The content of the thermosetting resin (A) in the thermosetting resin composition of the present embodiment is not particularly limited, but from the viewpoints of high-frequency characteristics, heat resistance, and moldability, it is preferably 5 to 95 mass%, more preferably 10 to 80 mass%, even more preferably 10 to 60 mass%, and particularly preferably 15 to 40 mass%, based on the total amount of solids in the thermosetting resin composition.

[0021] ((B) One or more high dielectric constant inorganic fillers selected from the group consisting of titanium-based inorganic fillers and zircon-based inorganic fillers) From the viewpoint of the dielectric constant (Dk), the titanium-based inorganic filler is preferably one or more selected from the group consisting of titanium dioxide and metal titanates. From the viewpoint of the dielectric constant (Dk), the metal titanates include alkali metal titanates such as potassium titanate; alkaline earth metal titanates such as barium titanate, calcium titanate, and strontium titanate; and lead titanate. From the viewpoint of the dielectric constant (Dk), the metal titanates are preferably one or more selected from these examples, and from the viewpoint of the dielectric constant (Dk), alkaline earth metal titanates are more preferable, and calcium titanate and strontium titanate are even more preferable. From the viewpoint of the dielectric constant (Dk), the zircon-based inorganic filler is preferably an alkali metal zirconate. From the viewpoint of the dielectric constant (Dk), the alkali metal zirconate is preferably one or more selected from the group consisting of calcium zirconate and strontium zirconate. From the viewpoints of dielectric loss tangent (Df) and specific gravity, the component (B) is preferably a titanium-based inorganic filler, and more preferably, the titanium-based inorganic filler is as described above. As the component (B), one type may be used alone, or two or more types may be used in combination.

[0022] There are no particular limitations on the shape of component (B); however, since industrially available high dielectric constant inorganic fillers generally tend to be irregular in shape, component (B) may be irregular in shape, but it may also be spherical or have another shape.

[0023] The average particle size of the (B) component is not particularly limited, but is preferably 1.0 μm or more. When the average particle size of the (B) component is 1.0 μm or more, the heat resistance tends to be significantly improved. From the same viewpoint, the average particle size of the (B) component is preferably 1.3 μm or more, more preferably 1.5 μm or more, and even more preferably 1.8 μm or more. From the viewpoint of eliminating coarse particles that may cause insulation failure, the upper limit of the average particle size of the (B) component is preferably 4.0 μm or less, more preferably 3.5 μm or less, even more preferably 3.0 μm or less, and particularly preferably 2.5 μm or less. From the above, the average particle size of component (B) may be 1.0 to 4.0 μm, 1.3 to 3.5 μm, 1.5 to 3.0 μm, or 1.3 to 2.5 μm. The lower and upper limits of the numerical range can be changed based on the above description. In this disclosure, the particle size refers to the primary particle size. The average particle size of component (B) is the d50 value (median size of volume distribution) obtained by analyzing the particle size distribution using a particle size distribution measuring device.

[0024] Incidentally, thermosetting resin compositions used in antenna devices, printed wiring boards, and the like are generally used after filtering through a mesh with a predetermined mesh size in order to remove metal foreign matter that may cause insulation defects. For this reason, it is preferable that no clogging occurs when the varnish is filtered through a #200 mesh (mesh size: 75 μm). Hereinafter, the ease with which a varnish of a thermosetting resin composition passes through a mesh when filtered through the mesh is referred to as "mesh passability." From the viewpoint of mesh passing, the total content of particles having a particle size of 1.0 μm or less in component (B) is preferably 30 vol% or less, more preferably 28 vol% or less, and even more preferably 25 vol% or less, based on component (B). There is no particular lower limit for the total content of particles having a particle size of 1.0 μm or less, and it may be 0 vol%, 5 vol% or more, 10 vol% or more, or 15 vol% or more. From the above, the total content of particles having a particle size of 1.0 μm or less in component (B) may be 0 to 30 volume %, 0 to 28 volume %, 5 to 25 volume %, or 10 to 25 volume % relative to the total particles in component (B). The lower and upper limits of the numerical range can be changed based on the above description. The total content of particles having a particle diameter of 1.0 μm or less in component (B) can be determined by analyzing the particle size distribution of component (B) using a particle size distribution measuring device and calculating the cumulative frequency of particles having a particle diameter of 1.0 μm or less. The method and conditions for analyzing the particle size distribution may be specifically described in the Examples. It is also possible to observe the cross section of the cured product of the thermosetting resin composition under a microscope and classify the particles in the image according to particle diameter, thereby calculating the proportion of particles having a particle diameter of 1.0 μm or less, and thus determining the total content of particles having a particle diameter of 1.0 μm or less in component (B).

[0025] There is no particular limitation on the method for adjusting the total content of particles with a particle diameter of 1.0 μm or less, but examples thereof include a classification method, a method for adjusting the pulverization method, and the like. In the classification method, particles with a particle diameter of 1.0 μm or less can be easily reduced by sieving. In addition, in the method for adjusting the pulverization method, one or more high dielectric constant inorganic fillers selected from the group consisting of titanium-based inorganic fillers and zircon-based inorganic fillers can be pulverized with a pulverizer such as a ball mill or a jet mill so as not to generate particles with a particle diameter of 1.0 μm or less, and as a result, particles with a particle diameter of 1.0 μm or less can be easily reduced.

[0026] In addition, although not particularly limited, from the viewpoint of mesh passing, the content of particles having a particle diameter of 1.0 μm in the (B) component is preferably 4.5 vol% or less, more preferably 4 vol% or less, even more preferably 3.5 vol% or less, and particularly preferably 3.4 vol% or less, based on the total particles of the (B) component. There is no particular limit to the lower limit of the content of particles having a particle diameter of 1.0 μm, and it may be 2 vol% or more, 2.5 vol% or more, or 2.7 vol% or more. From the above, the content of particles having a particle diameter of 1.0 μm in the (B) component may be 2 to 4.5 volume % relative to the total particles of the (B) component, and the lower and upper limits of this numerical range can be changed based on the above description. The content of particles having a particle diameter of 1.0 μm can be determined from the frequency of particles having a particle diameter of 1.0 μm by analyzing the particle size distribution of component (B) using a particle size distribution measuring device. The method and conditions for analyzing the particle size distribution may be, in detail, the same as those described in the Examples.

[0027] (B) Component Content The content of the (B) component in the thermosetting resin composition of the present embodiment is not particularly limited, but from the viewpoint of the relative dielectric constant (Dk), it is preferably 1 to 60% by volume, more preferably 2 to 30% by volume, may be 3 to 20% by volume, may be 7 to 30% by volume, or may be 12 to 25% by volume, based on the total solid content in the thermosetting resin composition. When the content of the (B) component is described in terms of mass%, it is preferably 5 to 95% by mass, more preferably 15 to 90% by mass, even more preferably 20 to 70% by mass, particularly preferably 20 to 55% by mass, and most preferably 25 to 50% by mass, based on the total solid content in the thermosetting resin composition. When the content of the (B) component in the thermosetting resin composition of the present embodiment is equal to or more than the lower limit, the relative dielectric constant (Dk) tends to be high, and when the content is equal to or less than the upper limit, the dielectric loss tangent (Df) tends to be prevented from becoming too high.

[0028] ((X) Molybdenum Compounds) The component (X) is not particularly limited as long as it is a compound containing molybdenum element, but from the viewpoint of improving drill machinability, it is preferably one or more compounds selected from the group consisting of molybdenum oxides, molybdic acid compounds, molybdenum boride, molybdenum disilicide, molybdenum nitride, and molybdenum carbide. The molybdenum oxide includes molybdenum trioxide. Examples of the molybdic acid compound include zinc molybdate, ammonium molybdate, magnesium molybdate, calcium molybdate, barium molybdate, sodium molybdate, potassium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, and silicomolybdic acid.

[0029] As the component (X), from the viewpoint of improving drill machinability, a molybdic acid compound is preferable, zinc molybdate, ammonium molybdate, magnesium molybdate, calcium molybdate, barium molybdate, sodium molybdate, and potassium molybdate are more preferable, and zinc molybdate is even more preferable. The molybdenum compound may be supported on a carrier, and is preferably supported on a carrier. When the molybdenum compound is supported on a carrier, it is possible to prevent the sedimentation of the (X) component and improve the dispersibility when the thermosetting resin composition is dissolved in an organic solvent to form a varnish, and as a result, the effect of improving drilling processability tends to be efficiently exhibited. Examples of the carrier include talc, silica, zinc oxide, calcium carbonate, magnesium hydroxide, etc. Among these, talc and silica are preferred, and talc is more preferred. For these reasons, zinc molybdate-supported talc is the most preferable component (X).

[0030] The average particle size of component (X) is not particularly limited, but is preferably 0.1 to 5 μm, more preferably 0.3 to 3.5 μm, and even more preferably 0.5 to 2.5 μm. When the average particle size of component (X) is equal to or greater than the lower limit, there is a tendency that a decrease in fluidity due to thickening can be suppressed, and when it is equal to or less than the upper limit, there is a tendency that an increase in the settling velocity of the particles can be suppressed. The shape of the (X) component is not particularly limited, and may be amorphous or may be spherical or other shapes.

[0031] In this embodiment, the effect of improving drill workability by blending the component (X) becomes more pronounced due to the presence of the high dielectric constant inorganic filler (B). As the component (X), one type may be used alone, or two or more types may be used in combination. As the component (X), a commercially available product can be used.

[0032] ((X) Content of molybdenum compounds) The content of the (X) component in the thermosetting resin composition of the present embodiment is not particularly limited, but is preferably 0.1 to 10% by volume, more preferably 0.3 to 7% by volume, and even more preferably 0.5 to 5% by volume, based on the total solid content in the thermosetting resin composition. The content of the (X) component, expressed in mass%, is preferably 0.5 to 15% by mass, more preferably 1.0 to 10% by mass, and even more preferably 1.0 to 8% by mass, based on the total solid content in the thermosetting resin composition. When the content of the (X) component in the thermosetting resin composition of the present embodiment is equal to or more than the above lower limit, the effect of improving drill processability tends to be high, and when the content is equal to or less than the above upper limit, the heat resistance and peel strength tend to be good.

[0033] The thermosetting resin composition of the present embodiment may further contain other components. The other components are not particularly limited, but preferably contain at least one selected from the group consisting of (C) elastomer, (D) inorganic filler (excluding (B) component and (X) component), coupling agent, (E) curing accelerator, (F) flame retardant, flame retardant assistant, antioxidant, adhesion improver, heat stabilizer, antistatic agent, ultraviolet absorber, pigment, colorant, and lubricant.

[0034] ((C) Elastomer) The thermosetting resin composition of the present embodiment is not particularly limited, but preferably further contains an elastomer (C). Examples of component (C) include styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, polyester-based elastomers, polyamide-based elastomers, acrylic-based elastomers, silicone-based elastomers, etc. These elastomers are composed of a hard segment component and a soft segment component, and generally, the hard segment component contributes to heat resistance and strength, and the soft segment component contributes to flexibility and toughness. The component (C) may be used alone or in combination of two or more types.

[0035] From the viewpoint of high frequency characteristics, the (C) component is preferably a styrene-based elastomer, and more preferably a styrene-based thermoplastic elastomer. The styrene-based elastomer may have a structural unit derived from a styrene-based compound, and from the viewpoints of high frequency characteristics, adhesion to a conductor, heat resistance, and low thermal expansion, it is preferable to use at least one selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymers (SEBS, SBBS), hydrogenated styrene-isoprene-styrene block copolymers (SEPS), and styrene-maleic anhydride copolymers (SMA), more preferably at least one selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymers (SEBS) and hydrogenated styrene-isoprene-styrene block copolymers (SEPS), and even more preferably hydrogenated styrene-butadiene-styrene block copolymers (SEBS). The styrene-based elastomer (excluding the SMA) may be modified with an acid anhydride such as maleic anhydride, and examples of such elastomers include SEBS modified with an acid anhydride such as maleic anhydride, and SEPS modified with an acid anhydride such as maleic anhydride. The acid value of the acid-modified styrene-based elastomer (excluding the SMA) is not particularly limited, but is preferably 2 to 20 mg CH3ONa / g, more preferably 5 to 15 mg CH3ONa / g, and even more preferably 7 to 13 mg CH3ONa / g.

[0036] In the styrene-based elastomer, the content of structural units derived from styrene [hereinafter, may be referred to as "styrene content"] is not particularly limited, but from the viewpoints of high-frequency characteristics, adhesion to a conductor, heat resistance, and low thermal expansion, it is preferably 5 to 80 mass%, more preferably 10 to 75 mass%, further preferably 15 to 60 mass%, and particularly preferably 20 to 45 mass%. The weight average molecular weight (Mw) of the styrene-based elastomer is not particularly limited, but is preferably 12,000 to 1,000,000, more preferably 30,000 to 500,000, further preferably 50,000 to 120,000, and particularly preferably 70,000 to 100,000. The weight average molecular weight (Mw) means a value measured in terms of polystyrene by gel permeation chromatography (GPC). The melt flow rate (MFR) of the styrene-based elastomer is not particularly limited, but is preferably 0.1 to 20 g / 10 min, more preferably 1 to 15 g / 10 min, further preferably 2 to 10 g / 10 min, and particularly preferably 3 to 7 g / 10 min, measured under conditions of 230° C. and a load of 2.16 kgf (21.2 N).

[0037] (C) Elastomer Content When the thermosetting resin composition of the present embodiment contains the component (C), its content is not particularly limited, but is preferably 1 to 20 mass%, more preferably 2 to 15 mass%, and even more preferably 3 to 10 mass%, based on the total solid content in the thermosetting resin composition. When the content of the component (C) is equal to or more than the lower limit, better high-frequency characteristics tend to be obtained, and when it is equal to or less than the upper limit, good heat resistance, moldability, processability, and flame retardancy tend to be obtained.

[0038] ((D) Inorganic filler) The thermosetting resin composition of the present embodiment is not particularly limited, but preferably further contains (D) an inorganic filler. The thermosetting resin composition of the present embodiment tends to have better low thermal expansion, high elastic modulus, heat resistance, and flame retardancy by containing the component (D), provided that the component (D) does not contain the component (B). The component (D) may be used alone or in combination of two or more types.

[0039] Examples of the (D) component include silica, alumina, mica, beryllia, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, clay such as calcined clay, talc, aluminum borate, silicon carbide, etc. Among these, from the viewpoint of low thermal expansion, elastic modulus, heat resistance and flame retardancy, it is preferable to include one or more selected from the group consisting of silica, alumina, mica and talc, it is preferable to include one or more selected from the group consisting of silica and alumina, and it is more preferable to include silica. Examples of silica include crushed silica, fumed silica, fused silica, etc. Among these, fused silica is preferable, and fused spherical silica is more preferable.

[0040] There are no particular limitations on the average particle size of component (D), but it is preferably from 0.01 to 20 μm, more preferably from 0.1 to 10 μm, even more preferably from 0.2 to 3 μm, and particularly preferably from 0.3 to 1 μm.

[0041] (D) Inorganic filler content When the thermosetting resin composition of the present embodiment contains an inorganic filler, the content thereof is not particularly limited, but in any case, from the viewpoints of thermal expansion coefficient, elastic modulus, heat resistance, and flame retardancy, the content thereof is preferably 3 to 70 volume %, more preferably 5 to 65 volume %, even more preferably 5 to 60 volume %, even more preferably 10 to 50 volume %, particularly preferably 10 to 40 volume %, and most preferably 10 to 30 volume %, relative to the total amount of solids in the thermosetting resin composition. The content of the (D) component, in terms of mass%, is preferably 1 to 60 mass%, more preferably 5 to 50 mass%, even more preferably 10 to 45 mass%, particularly preferably 15 to 45 mass%, and most preferably 15 to 35 mass%, relative to the total amount of solids in the thermosetting resin composition.

[0042] When an inorganic filler is used, a coupling agent may be used in combination as necessary to improve the dispersibility of the inorganic filler and the adhesion between the inorganic filler and the organic component in the resin composition. Examples of the coupling agent include a silane coupling agent and a titanate coupling agent. One type of coupling agent may be used alone, or two or more types may be used in combination. When a coupling agent is used, the treatment method may be a so-called integral blend treatment method in which the inorganic filler is blended in the resin composition and then the coupling agent is added, but it is preferable to use an inorganic filler that has been surface-treated in advance with a coupling agent in a dry or wet manner. By adopting this method, the characteristics of the inorganic filler can be more effectively expressed. If necessary, the inorganic filler may be used in the form of a slurry in which it is dispersed in an organic solvent in advance.

[0043] ((E) Curing Accelerator) The thermosetting resin composition of the present embodiment is not particularly limited, but preferably further contains (E) a curing accelerator. Examples of the (E) component include amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, organometallic salts, acid catalysts, and organic peroxides. In this embodiment, imidazole-based curing accelerators are not classified as amine-based curing accelerators. The curing accelerators may be used alone or in combination of two or more. As the curing accelerator, amine-based curing accelerators, imidazole-based curing accelerators, and phosphorus-based curing accelerators are preferred. Examples of the amine-based curing accelerator include amine compounds having a primary to tertiary amino group, such as triethylamine, 4-aminopyridine, tributylamine, and dicyandiamide; and quaternary ammonium compounds. Examples of the imidazole-based curing accelerator include imidazole compounds such as methylimidazole, phenylimidazole, 2-undecylimidazole, and isocyanate-masked imidazole (for example, an addition reaction product of hexamethylene diisocyanate resin and 2-ethyl-4-methylimidazole). Examples of the phosphorus-based curing accelerator include tertiary phosphines such as triphenylphosphine; and quaternary phosphonium compounds such as an addition product of p-benzoquinone and tri-n-butylphosphine.

[0044] ((E) Content of hardening accelerator) When the thermosetting resin composition of the present embodiment contains the component (E), its content is not particularly limited, but in any case, it is preferably 0.01 to 3 mass%, more preferably 0.05 to 2.5 mass%, further preferably 0.1 to 2.5 mass%, particularly preferably 0.5 to 2.3 mass%, based on the total amount of resin components in the thermosetting resin composition. When the content of the component (E) is within the above range, better high frequency characteristics, heat resistance, storage stability, and moldability tend to be obtained.

[0045] ((F) Flame retardants) The thermosetting resin composition of the present embodiment is not particularly limited, but preferably further contains (F) a flame retardant. Examples of the (F) component include inorganic phosphorus-based flame retardants, organic phosphorus-based flame retardants, and metal hydrates such as aluminum hydroxide hydrate and magnesium hydroxide hydrate. Metal hydroxides may also be classified as inorganic fillers, but metal hydroxides that can impart flame retardancy are classified as flame retardants. Among these, organic phosphorus-based flame retardants are preferred as the (F) component. Examples of organic phosphorus-based flame retardants include aromatic phosphoric acid esters, phosphonic acid diesters, and phosphinic acid esters; metal salts of phosphinic acid, organic nitrogen-containing phosphorus compounds, and cyclic organic phosphorus compounds. Here, examples of the "metal salt" include lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, aluminum salts, titanium salts, and zinc salts. Among these, aromatic phosphorus esters are preferred as organic phosphorus-based flame retardants.

[0046] (F) Flame retardant content When the thermosetting resin composition of the present embodiment contains the (F) component, its content is not particularly limited, but in any case, it is preferably 0.1 to 30 mass%, may be 1 to 25 mass%, may be 3 to 20 mass%, or may be 7 to 15 mass% based on the total solid content in the thermosetting resin composition. When the content of the (F) component is equal to or more than the lower limit, better flame retardancy tends to be obtained. When the content is equal to or less than the upper limit, better moldability, adhesion to a conductor, and better heat resistance tend to be obtained.

[0047] (Content of ingredients other than the above ingredients) When the thermosetting resin composition of the present embodiment contains components other than the above components (flame retardant aid, antioxidant, adhesion improver, heat stabilizer, antistatic agent, UV absorber, pigment, colorant, lubricant, and other components), the content of each of these is not particularly limited, and may be, for example, 0.01 parts by mass or more, 10 parts by mass or less, 5 parts by mass or less, 1 part by mass or less, or none at all, relative to 100 parts by mass of the total amount of the resin components of the thermosetting resin composition.

[0048] (Organic solvent) The thermosetting resin composition of the present embodiment may be a so-called "varnish" containing an organic solvent, from the viewpoint of facilitating handling and of facilitating production of a prepreg, which will be described later. The organic solvent is not particularly limited, but includes alcohol-based solvents such as ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as tetrahydrofuran; aromatic solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; sulfur-containing solvents such as dimethyl sulfoxide; and ester-based solvents such as γ-butyrolactone. From the viewpoint of solubility, ketone-based solvents are preferred, and methyl isobutyl ketone is more preferred. The organic solvent may be used alone or in combination of two or more kinds.

[0049] When the thermosetting resin composition of the present embodiment is used as a varnish, the solid content is preferably 30 to 90 mass%, more preferably 40 to 80 mass%, and even more preferably 55 to 70 mass%. When the solid content of the thermosetting resin composition is within the above range, the thermosetting resin composition is easy to handle, the impregnation into the substrate and the appearance of the produced prepreg are good, and the coating property when the resin film is produced is also good.

[0050] The thermosetting resin composition of the present embodiment can be produced by mixing the (A), (B) and (X) components, as well as the above components that may be used as necessary, by a known method. At this time, each component may be dissolved or dispersed in the organic solvent while stirring. The mixing order, temperature, time and other conditions are not particularly limited and can be set as desired. The thermosetting resin composition of the present embodiment can exhibit a high relative dielectric constant (Dk) and a low dielectric tangent (Df), and is therefore useful for antenna modules, in particular for miniaturized antenna modules compatible with the fifth generation mobile communication system (5G).

[0051] [Prepreg] The prepreg of the present embodiment is a prepreg containing the thermosetting resin composition of the present embodiment or a semi-cured product of the thermosetting resin composition. The prepreg of the present embodiment can exhibit a high relative dielectric constant (Dk) and a low dielectric loss tangent (Df), and is therefore useful for antenna modules, particularly for miniaturized antenna modules compatible with 5G. The prepreg of this embodiment contains, for example, the thermosetting resin composition of this embodiment or a semi-cured product of the thermosetting resin composition and a sheet-like fiber substrate. The prepreg is formed using the thermosetting resin composition of this embodiment and a sheet-like fiber substrate, and can be obtained, for example, by impregnating or coating the thermosetting resin composition of this embodiment into a sheet-like fiber substrate, drying it, and semi-curing (B-stage) as necessary. More specifically, for example, the prepreg of this embodiment can be produced by heating and drying it in a drying oven at a temperature of 80 to 200 ° C. for 1 to 30 minutes to semi-cure (B-stage). Here, in the present disclosure, B-stage refers to bringing it into a B-stage state defined in JIS K6900 (1994). The amount of the thermosetting resin composition used can be appropriately determined so that the solid content concentration derived from the thermosetting resin composition in the prepreg after drying is 30 to 90 mass %. By setting the solid content concentration in the above range, better moldability tends to be obtained when the laminate is made.

[0052] As the sheet-like fiber substrate of the prepreg, a known one used in various laminates for electrical insulating materials is used. The material of the sheet-like fiber substrate includes inorganic fibers such as E glass, D glass, S glass, and Q glass; organic fibers such as polyimide, polyester, and tetrafluoroethylene; and mixtures thereof. These sheet-like fiber substrates have shapes such as woven fabric, nonwoven fabric, roving, chopped strand mat, and surfacing mat.

[0053] The thickness of the prepreg is not particularly limited, and may be 10 to 170 μm, 10 to 120 μm, or 10 to 70 μm.

[0054] [Resin film] The resin film of the present embodiment is a resin film containing the thermosetting resin composition of the present embodiment or a semi-cured product of the thermosetting resin composition. The resin film of the present embodiment can exhibit a high relative dielectric constant (Dk) and a low dielectric loss tangent (Df), and is therefore useful for antenna modules, particularly for miniaturized antenna modules compatible with 5G. The resin film of this embodiment can be produced, for example, by applying a thermosetting resin composition containing an organic solvent, i.e., a varnish, to a support, heating and drying it, and semi-curing (B-staging) as necessary. The support may be a plastic film, a metal foil, or a release paper. The drying temperature and drying time may be appropriately determined depending on the amount of organic solvent used and the boiling point of the organic solvent used, but a resin film can be suitably formed by drying at 50 to 200°C for about 1 to 10 minutes.

[0055] [Laminate] The laminate of the present embodiment is a laminate having a cured product of the thermosetting resin composition of the present embodiment or a cured product of the prepreg and a metal foil. The laminate has a high relative dielectric constant (Dk) and a low dielectric loss tangent (Df), and is therefore useful for antenna modules, particularly for miniaturized antenna modules compatible with 5G. The laminate of the present embodiment can be produced, for example, by placing metal foil on one or both sides of a prepreg obtained by stacking two or more prepregs of the present embodiment, or by placing metal foil on one or both sides of a prepreg obtained by stacking a total of two or more prepregs of the present embodiment and a prepreg other than the present embodiment, and then hot-pressing and molding. In the laminate obtained by this production method, the prepreg of the present embodiment is C-staged. In this disclosure, C-stage refers to bringing the prepreg into the C-stage state defined in JIS K6900 (1994). Note that a laminate having metal foil is sometimes called a metal-clad laminate. The metal of the metal foil is not particularly limited, but from the viewpoint of electrical conductivity, it may be copper, gold, silver, nickel, platinum, molybdenum, ruthenium, aluminum, tungsten, iron, titanium, chromium, or an alloy containing one or more of these metal elements, with copper and aluminum being preferred, and copper being more preferred. The conditions for hot and pressure molding are not particularly limited, but may be, for example, a temperature of 100 to 300° C., a pressure of 0.2 to 10 MPa, and a time of 0.1 to 5 hours. In addition, the hot and pressure molding may be performed using a vacuum press or the like to maintain a vacuum state for 0.5 to 5 hours.

[0056] [Printed wiring board] The printed wiring board of this embodiment has one or more selected from the group consisting of the cured product of the thermosetting resin composition of this embodiment, the cured product of the prepreg of this embodiment, and the laminate of this embodiment. The printed wiring board of this embodiment can be manufactured by performing a circuit formation process by drilling, metal plating, etching of metal foil, etc., using one or more selected from the group consisting of the prepreg of this embodiment, the resin film of this embodiment, and the laminate of this embodiment by a known method. In addition, a multilayer printed wiring board can be manufactured by further performing a multilayer adhesion process as necessary. In the printed wiring board of this embodiment, the prepreg of this embodiment or the resin film of this embodiment is C-staged.

[0057] [Antenna device] The present disclosure also provides an antenna device having the laminate or printed wiring board of the present embodiment. The antenna device may be one in which one laminate or a plurality of laminates or printed wiring boards are installed. There is no particular limitation on the manner in which the plurality of antenna elements are installed, but it is preferable to arrange them in a two-dimensional array, for example. The configuration of the antenna device is not particularly limited, but for example, Japanese Patent Publication No. 6777273 and the like can be referred to.

[0058] Considering use as an antenna module, the laminate or printed wiring board in the antenna device preferably has conductor patterns such as a power supply conductor pattern, a ground conductor pattern, and a short-circuit conductor. The short-circuit conductor is a conductor that shorts the power supply conductor pattern and the ground conductor pattern, and is provided in a via hole portion described later. The conductive pattern is preferably made of a metal containing, as a main component, copper, aluminum, gold, silver, or an alloy thereof.

[0059] The laminate or printed wiring board in the antenna device preferably has a via hole, which allows the short-circuiting conductor to be formed and enables electrical continuity between the power supply conductor pattern and the ground conductor pattern. There is no particular limitation on the method for forming the via holes, and it is possible to use a method using a laser, plasma, or a combination of these, etc. As the laser, it is possible to use a carbon dioxide laser, a YAG laser, a UV laser, an excimer laser, etc. After the via holes are formed, a desmear treatment or the like may be performed using an oxidizing agent. Examples of the oxidizing agent include, preferably, permanganates such as potassium permanganate and sodium permanganate, dichromates, ozone, hydrogen peroxide-sulfuric acid, and nitric acid, more preferably, permanganates, and further preferably, an aqueous solution of sodium hydroxide of a permanganate, i.e., an aqueous solution of alkaline permanganate. In addition, it is preferable that the laminate or printed wiring board in the antenna device is one in which a short-circuit conductor is formed in the via hole after the via hole is formed. The conductor used here is preferably made of the same metal as the metal forming the conductor pattern.

[0060] [Antenna module] The present disclosure also provides an antenna module having a power supply circuit and the antenna device of the present embodiment. The power supply circuit is not particularly limited, but may be an RFIC (Radio Frequency Integrated Circuit) or the like. The RFIC includes a switch, a power amplifier, a low-noise amplifier, an attenuator, a phase shifter, a signal combiner-demultiplexer, a mixer, an amplifier circuit, and the like. A high-frequency signal supplied from an RFIC is transmitted to the feeding point of the feeding conductor via a short-circuiting conductor formed in a via of the antenna module laminate. The configuration of the antenna module is not particularly limited, but for example, Japanese Patent No. 6777273 and the like can be referred to.

[0061] [Communication Device] Furthermore, the present disclosure also provides a communication device having a baseband signal processing circuit and the antenna module of the present embodiment. The communication device of this embodiment can upconvert a signal transmitted from the baseband signal processing circuit to the antenna module into a high-frequency signal and radiate it from the antenna device, and can downconvert a high-frequency signal received by the antenna device and process the signal in the baseband signal processing circuit.

[0062] Although preferred embodiments have been described above, these are merely examples for the purpose of explaining the present disclosure, and the scope of the present disclosure is not limited to these embodiments. The present disclosure also includes various aspects different from the above-described embodiments, provided that they do not deviate from the gist of the disclosure. EXAMPLES

[0063] The present embodiment will be specifically described below with reference to examples, although the present embodiment is not limited to the following examples.

[0064] In each example, the weight average molecular weight (Mw) was measured by the following method. (Method of measuring weight average molecular weight (Mw)) The values ​​were calculated from a calibration curve using standard polystyrene by gel permeation chromatography (GPC). The calibration curve was approximated by a third-order equation using standard polystyrene: TSKstandard POLYSTYRENE (Type; A-2500, A-5000, F-1, F-2, F-4, F-10, F-20, F-40) [manufactured by Tosoh Corporation, product name]. The measurement conditions for GPC are shown below. Device: Pump: L-6200 type [manufactured by Hitachi High-Technologies Corporation] Detector: L-3300 type RI [Hitachi High-Technologies Corporation] Column oven: L-655A-52 [Hitachi High-Technologies Corporation] Column: Guard column: TSK Guardcolumn HHR-L + column: TSKgel G4000HHR + TSKgel G2000HHR (all manufactured by Tosoh Corporation, product names) Column size: 6.0 x 40 mm (guard column), 7.8 x 300 mm (column) Eluent: Tetrahydrofuran Sample concentration: 30mg / 5mL Injection volume: 20μL Flow rate: 1.00mL / min Measurement temperature: 40℃

[0065] Furthermore, for the components (B) and (X) used in each example, the particle size distribution was measured and the average particle size was calculated by the following method. (Method of measuring particle size distribution) Potter-type homogenizer (volume 10 cm 3 0.15 g of component (B) (or component (X)) and 0.1 ml of sodium hexametaphosphate were added to the mixture and crushed for 1 minute. The crushed mixture was then added to 50 ml of water filtered through a 1 μm filter, and treated in an ultrasonic bath for 3 minutes to prepare a sample for evaluation. Using 5-10 ml of the evaluation sample prepared above, the particle size distribution was measured using a particle size distribution measuring device "Microtrac MT3300EXII" (manufactured by Microtrac-Bell Co., Ltd.). Water (containing 0.1 mass% sodium hexametaphosphate) was used as the measurement solvent, the measurement mode was transmission, and the measurement time was 30 seconds. The measurement was performed twice, and the average value of the two measurements was taken as the particle size distribution of the (B) component (or (X) component) contained in the evaluation sample.

[0066] [Production Example 1: Production of modified maleimide compound] In a 5L reaction vessel equipped with a thermometer, a stirrer, and a water content meter with a reflux condenser, capable of heating and cooling, 100 parts by mass of 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 5.6 parts by mass of a siloxane compound (functional group equivalent: 750 g / mol) having amino groups at both ends, 7.9 parts by mass of 3,3'-diethyl-4,4'-diaminodiphenylmethane, and 171 parts by mass of propylene glycol monomethyl ether were added and reacted for 2 hours under reflux. This was concentrated at the reflux temperature for 3 hours to produce a modified maleimide compound solution with a solid content concentration of 65% by mass. The weight average molecular weight (Mw) of the obtained modified maleimide compound was about 2,700.

[0067] [Examples 1 to 3, Comparative Examples 1 to 2] Each component shown in Table 1 was stirred and mixed at room temperature together with 58 parts by mass of toluene and 10 parts by mass of methyl isobutyl ketone according to the formulation shown in Table 1 to prepare a thermosetting resin composition (varnish) having a solid content concentration of 60 to 65 mass%, and the mixture was filtered using a nylon mesh with a #200 mesh (opening size of 75 μm) to obtain a filtrate. The filtrate obtained above was applied to a 0.08 mm thick glass cloth (E glass, manufactured by Nitto Boseki Co., Ltd.), which was then heated and dried at 150° C. for 5 minutes to produce a prepreg with a solid content of about 47% by mass derived from the thermosetting resin composition. Low-profile copper foil with a thickness of 18 μm (Rz of M surface: 1.5 μm) was placed on the top and bottom of this prepreg so that the M surface (matte surface) was in contact with the prepreg, and then heated and pressurized for 90 minutes at a temperature of 230° C., a pressure of 3.0 MPa, and a time of 90 minutes to produce a double-sided copper-clad laminate (thickness: 0.10 mm). The varnish or double-sided copper-clad laminate obtained in each example was evaluated according to the following methods. The results are shown in Table 1.

[0068] [Evaluation of double-sided copper-clad laminates] (1. Drilling workability (hole position accuracy)) Two double-sided copper-clad laminates obtained in each example were stacked on top of each other, with a 0.1 mm thick aluminum foil placed on top and a 1.5 mm thick paper phenolic plate placed underneath. The plates were then drilled at a speed of 160 km / min using a drill with a diameter of 0.2 mm (Via Mechanics Co., Ltd., ND-1V212). -1 6,000 holes were drilled under the conditions of a feed rate of 2 m / min and a chip load of 12.5 μm / rev, and the hole position accuracy was measured using the following method as an index of drill workability. Of the two double-sided copper-clad laminates, the amount of hole misalignment on the bottom side (drill exit side) of the second sheet was measured using a hole position accuracy measuring device (HT-1AM, manufactured by Via Mechanics Co., Ltd.), and the hole position accuracy was calculated as the average + 3σ (σ: standard deviation) of the hole misalignment amounts for the 4,001st to 6,000th hits (unit: μm).

[0069] [Varnish Evaluation] (2. Mesh removal) As described above, the varnish obtained in each example was filtered using a nylon mesh of #200 mesh (openings 75 μm). At this time, without any additional manipulation, the state of filtration was visually observed and evaluated according to the following evaluation criteria. A: It was filtered cleanly. C: Clogging occurred and filtration stopped.

[0070] [Table 1]

[0071] Each component listed in Table 1 is explained below. [(A) Thermosetting resin] A-1: Modified maleimide compound obtained in Production Example 1 A-2: Polyphenylene ether with methacryloyl groups at both ends of the molecule (weight average molecular weight 1,700)

[0072] [(B) High dielectric constant inorganic filler] B-1: Calcium titanate (total content of particles with a particle diameter of 1.0 μm or less: 21 vol%, content of particles with a particle diameter of 1.0 μm: 3.1 vol%, average particle diameter (d50): 2.1 μm)

[0073] [(X) Molybdenum compounds] X-1: Zinc molybdate supported talc (average particle size (d50); 2.0 μm)

[0074] [(C) Elastomer: styrene-based thermoplastic elastomer] C-1: Maleic anhydride modified hydrogenated styrene-based thermoplastic elastomer (maleic anhydride modified SEBS), acid value 10mgCH3ONa / g, styrene content 30%, MFR 5.0g / 10min (measurement conditions for said MFR: measured in accordance with ISO1133-1 (2011) at 230℃ and load 2.16kg).

[0075] [(D) Inorganic filler] D-1: Spherical fused silica, average particle size (d50); 1.5 μm, 50 mass% slurry (solvent: toluene)

[0076] [(E) Curing accelerator] E-1: 2-Undecylimidazole E-2: p-Benzoquinone and tri-n-butylphosphine adduct E-3: Dicyandiamide

[0077] [Flame retardant] F-1: Phosphate ester flame retardant with the following structural formula [ka]

[0078] From the results in Table 1, Examples 1 to 3 have extremely excellent drilling processability compared to Comparative Examples 1 and 2. In particular, it can be seen that the drilling processability improvement effect of Examples 1 to 3 is remarkable compared to Comparative Example 1 in which (B) high dielectric constant inorganic filler was not blended but (X) molybdenum compound was blended. Furthermore, in each example in which calcium titanate having a total content of particles with a particle size of 1.0 μm or less of about 21 volume % was used as component (B), excellent mesh-penetration properties were obtained.

Claims

1. (A) a thermosetting resin, and (B) one or more high dielectric constant inorganic fillers selected from the group consisting of titanium-based inorganic fillers and zircon-based inorganic fillers; A thermosetting resin composition comprising: The thermosetting resin composition further contains (X) a molybdenum compound.

2. 2. The thermosetting resin composition according to claim 1, wherein the component (X) is at least one selected from the group consisting of molybdenum oxides, molybdic acid compounds, molybdenum boride, molybdenum disilicide, molybdenum nitride, and molybdenum carbide.

3. 3. The thermosetting resin composition according to claim 2, wherein the molybdenum oxide is molybdenum trioxide.

4. 3. The thermosetting resin composition according to claim 2, wherein the molybdic acid compound is at least one selected from the group consisting of zinc molybdate, ammonium molybdate, magnesium molybdate, calcium molybdate, barium molybdate, sodium molybdate, potassium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, and silicomolybdic acid.

5. 2. The thermosetting resin composition according to claim 1, wherein the titanium-based inorganic filler is at least one selected from the group consisting of titanium dioxide and metal titanates.

6. 6. The thermosetting resin composition according to claim 5, wherein the metal titanate is at least one selected from the group consisting of alkali metal titanates, alkaline earth metal titanates, and lead titanate.

7. 2. The thermosetting resin composition according to claim 1, wherein the zircon-based inorganic filler is an alkali metal zirconate.

8. The thermosetting resin composition according to claim 1, wherein the content of the component (X) is 0.1 to 10 volume % based on the total solid content in the thermosetting resin composition.

9. 2. The thermosetting resin composition according to claim 1, wherein the component (A) comprises at least one selected from the group consisting of an epoxy resin, a maleimide compound, a polyphenylene ether resin, a phenolic resin, a polyimide resin, a cyanate resin, an isocyanate resin, a benzoxazine resin, an oxetane resin, an amino resin, an unsaturated polyester resin, an allyl resin, a dicyclopentadiene resin, a silicone resin, a triazine resin, and a melamine resin.

10. 2. The thermosetting resin composition according to claim 1, wherein the component (A) contains a polyphenylene ether resin having ethylenically unsaturated bond-containing groups at both ends.

11. A prepreg comprising the thermosetting resin composition according to claim 1 or a semi-cured product of the thermosetting resin composition.

12. A resin film comprising the thermosetting resin composition according to claim 1 or a semi-cured product of the thermosetting resin composition.

13. A laminate comprising the cured product of the thermosetting resin composition according to claim 1 and a metal foil.

14. A printed wiring board having a cured product of the thermosetting resin composition according to claim 1.

15. An antenna device comprising the laminate according to claim 13.

16. An antenna module comprising a feeding circuit and an antenna device according to claim 15.

17. A communication device comprising a baseband signal processing circuit and an antenna module according to claim 16.

Citation Information

Patent Citations

  • Miniature antenna

    WO2005101574A1

Cited By

  • Resin composition, prepreg, resin-attached film, resin-attached metal foil, metal-clad laminated plate, and wiring board

    WO2025205272A1